The effectiveness of a computerized educational program Based on Concept Maps on The Development of Creative Thinking and School Achievement among First- grade Middle School Students - Al-Balawi, Amirah Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify the effectiveness of a computerized educational program based on concept maps in the development of creative thinking and the achievement of first- intermediate students in Al- Ahlia Development Schools in Riyadh for the computer subject, the quasi- experimental curriculum is experimental and control. An achievement test that was applied to a sample of (60) female students in the first intermediate grade at Al- Motoweroon Private Schools in Riyadh (30) experimental, (30) female controls. The results of the study showed that the computerized educational program based on concept maps contributed to the development of creative thinking and achievement for female students. On the scale as a whole, the experimental got an average of (41.6) compared to the control one (24.1). On the dimensional level, its average was (fluency: 16.5- 11.4), (flexibility: 20.2- 8.4) (originality: 5.35- 4.05) for both the experimental and the control; All of them are a function of empiricism. The program also contributed to increasing the achievement of the experimental with an average of (7.42) compared to (3.43) for the control group, and the difference was statistically significant and in favor of the experimental, which indicates the effectiveness of the program and its impact on developing the level of creative thinking skills among the study sample. Based on the results, the researcher recommended preparing programs that enrich creative thinking. For students, and the use of conceptual maps in teaching the computer course He urged those in charge of authoring the curricula to focus on the presence of concept maps in the curriculum, and to find a comprehensive evaluation system that does not depend on memorization only, and the need to develop courses, and hold training courses for teachers, in addition to proposals for complementary studies on the subject.
Keywords: concept maps; academic achievement; creative thinking; e- learning